Valuing the risks and returns to the spot LNG trading - Suenaga, Hiroaki (IAEE, 2007)
A recent increase in the level and volatility of regional gas prices has followed an extensive discussion on potential returns from short-term LNG trading and potentially fostering integration of geographically sparse regional gas markets. This paper examines the stochastic properties of US natural gas and crude oil prices and considers their implications for the risks and returns to spot LNG trading, as opposed to a conventional practice of trading under long-term supply/purchase arrangement, in the Asia-pacific region. The model of commodity price dynamics estimated for the daily spot prices of Henry Hub natural gas and crude oil (Brent) indicates strong seasonal pattern in mean and volatility of natural gas price whereas the crude oil price exhibits almost no seasonal variation in its level and volatility. After controlling for such seasonality, the two prices exhibit only moderate correlation. The simulation model constructed around the depicted price dynamics implies positive expected returns from arbitraging spatial price differences between Asia and the US whereas the volatility of revenue is only moderately higher for short-term trading than for forward contracting. Besides, while the option to choose from multiple regional markets increases the overall volatility of revenue from short term trading, it reduces the downside risk substantially, with the revenue exceeding the level under forward trading more than 90% of time. A positive return from the short-term LNG trading with reasonably low risk will provide an incentive to LNG producers in Asia-pacific region to shift from conventional long-term supply arrangement to short-term trading.